Regulatory framework of corporate control in Ukraine - Mykhailo Kuzheliev (Cхід)
Non-correspondence of current system of corporate control to modern corporate relation system's demand determines the study of its performing law and normative aspects. Current legislative background for corporate control system formation and means for smallholders' rights and interests protection in Ukraine are suggested. In particular, factors of minority stakeholders' rights brake by corporate management and major stakeholders are analysed, corporate control types are systemized by national corporate legislation. By the study of international experience on corporate control formation it is found that the efficiency of implementation and defence means for smallholders tightly depends on legislative warranties for their rights. Corporative legislation and court practice of corporative conflicts under European and American Corporate Model, under which all of the participants have the legislative liability, has particular interest for Ukraine. The nature of a stakeholder's interest implementation by implementation of his legal rights and interests as organization and legislative components is analyzed. It is determined that legislative element of stakeholder's rights' warranty is implemented inextricably to internal means for owner's rights. The notion of "stakeholder's rights warranty" is defined as a complex of legislative and organizational tools for implementation of owner's property and non-property rights, protection of broken rights. Principles for corporative control market formation in Ukraine and means for such subsystem of corporate relations are suggested. It is also suggested to introduce a responsibility for certain officers' actions leading to witting stakeholder's rights brake by The Civil Codex.